Analisis Kemudahan, Kepercayaan, dan Publikasi Pengaruh Minat Tiket.Com - Muhamad Difa Rizky Pradana; Retno Mulatsih; Wasi Sumarsono (Logistics and Supply Chain Insights, 2025)
This study analyzes the partial and simultaneous influence of four factors—Publication (X_1), Access Convenience (X_2), Perceived Ease of Use (X_3), and Trust (X_4)—on the dependent variable, Intention to Use/Purchase (Y) Tiket.com for airline ticket purchases in Semarang City.1 Using an associative quantitative method, data were collected from 100 Tiket.com users (N=100) and analyzed via Multiple Linear Regression (SPSS 25.0).1 The analysis confirmed that all four independent variables positively and significantly influence the Intention to Use (all t_{hitung} > t_{tabel} 1.98498).1 The variable Perceived Ease of Use (X_3) was identified as the most dominant factor, showing the highest regression coefficient (β = 0.375), suggesting that the intuitive and effort-free experience of the application is the primary psychological driver for adoption among Semarang users.1, The overall model demonstrated a very strong explanatory capability, with an Adjusted R^2 of 0.792. This means 79.2% of the variation in Intention to Use Tiket.com is jointly explained by these four variables, with 20.8% attributed to factors outside the model.1 Managerial implications suggest prioritizing user experience design, clear information presentation, and maintaining transaction security to convert high interest into committed use.